An electron momentum spectroscopy and density functional theory study of the outer valence electronic structure of stella-2,6-dione - Nixon, Kate; Wang, F.; Campbell, L.; Maddern, T.; Winkler, D.; Gleiter, Rolf; Löb, Patrick; Weigold, E.; Brunger, M. J. (Journal of physics. B, Atomic, molecular and optical physics, 2003)
We report on the first electron momentum spectroscopy (EMS) study into the outer valence electronic structure of the ground electronic state for the organic molecule stella-2,6-dione (C8H8O2). Experimentally measured binding-energy spectra are compared against a He(Iα) photoelectron spectroscopy result, while our derived momentum distributions (MDs) are compared against corresponding results from the plane wave impulse approximation (PWIA) level calculations. These computations employed density functional theory (DFT) basis states at the triple zeta valence polarization (TZVP) level, with a range of exchange-correlation (XC) functionals. A detailed comparison between the experimental and PWIA DFT-XC/TZVP calculated MDs enabled us to evaluate the accuracy of the various functionals, the Becke-Perdew (BP) XC functional being found to provide the most accurate description here. The importance of the through-bond interaction to the molecular orbitals (MOs) of stella-2,6-dione is demonstrated using the orbital imaging capability of EMS. Finally we show that the molecular geometry of this molecule, as derived from BP/TZVP, is in quite good agreement with corresponding independent experimental data.